Um defeito de cor, de Ana Maria Gonçalves: uma escrita de resistência: entrelaçamentos entre metaficção historiográfica, memória e religiosidade - Silva, Camila de Matos (2018)
This dissertation is dedicated to analyze the novel Um defeito de cor (2006) by Ana Maria Gonçalves, through the trails of historiographic metafiction, religiosity, and writing of black female authorship and by the traces of memory of the peoples of the African Diaspora. Ana Maria Gonçalves gives voice to Kehinde, narrator of the novel, an African woman of the old Dahomey Kingdom and that during her saga revisits much of Brazil's colonial period bringing to light facts of collective and individual memory that mark this historical period. We looked for in our work to highlight the issues that territorializam writing of black women on Brazilian soil, in contemporary times. We try to discuss here epistemic and ideological aspects that make us affirm the relevance of the novel Um defeito de cor (2006) as writing african-women's resistance, and for this purpose authors such as: Homi Bhabha, Paul Gilroy, Stuart Hall, Zilá Bernd, Paul Ricouer, Linda Hutcheon, Leda Maria Martins, Maurice Halbwachs, Reginaldo Prandi, among others. During the research and writing process we miss concepts that treat memory, woman and religion, so we decided to join oroboro with the concept of mnemonic devices. to treat the specificities found within the novel, creating the concept of: oroboro mnemônico, allowed us to analyze how human or spiritual cycles/transits are connected with the memory.